Identification of Antibiotic Producing Actinomycetes Isolated from Sediment in Basra, Iraq - Walaa Isaa Ghadhban; Ahmed Abd Burghal (International Journal of Pharma and Bio Sciences, 2020)
The increasing prevalence of commercial drug-resistant microbes is a worrisome issue that calls for the search for new antibiotics by isolating microbes that produces active secondary metabolites from diverse environments to obtain new strains and products. In the present study, 25 samples were obtained from marine and marshes sediments in Basrah city, Iraq. The screening revealed that 13 isolates possess antimicrobial activity. Three of these strains (W2, W5, and W11) were found to produce antibacterial and antifungal metabolites, W5 has maximum inhibition zone (28 and 22 mm) was selected against E. coli and Staphylococcus aureus respectively, W2 recorded 14 mm of inhibition zone against Aspergillus niger, while W11 has 13 mm of inhibition zone against Candida albicans. These isolates were identi?ed as Streptomyces sp. TRM46619 (W2), Micromonospora auratinigra SB29 (W5) and Streptomyces carpaticus PES-A23 (W11) depended on amplified 16S rDNA gene by using universal primers. All strains have broad antimicrobial activity against pathogenic bacteria gram-positive and gram-negative, as well as against fungi, and this indicates a promising potential for new antibiotics.